2010
DOI: 10.1136/ip.2010.029215.861
|View full text |Cite
|
Sign up to set email alerts
|

The effect of education and safety equipment on burn and scald prevention practices and on childhood thermal injuries: update of a systematic review and meta-analysis

Abstract: ObjectiveChildhood burns and scalds are a significant public health problem. This systematic review and meta-analysis evaluates whether home safety education and the provision of safety equipment increases burn and scald prevention practices and reduces thermal injuries.MethodA range of bibliographic databases were searched until April 2009. Search methods also included other electronic sources; hand searching of conference abstracts, IPJ and reference lists. We included randomised controlled trials (RCTs), no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Unfortunately, the investigators were only successful in obtaining IPD for a proportion of the studies. Additional details on the included studies can be found in related literature [10,11,19,20].…”
Section: Motivating Example: the Effectiveness Of Home Safety Educatimentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, the investigators were only successful in obtaining IPD for a proportion of the studies. Additional details on the included studies can be found in related literature [10,11,19,20].…”
Section: Motivating Example: the Effectiveness Of Home Safety Educatimentioning
confidence: 99%
“…">Motivating example: The effectiveness of home safety education and the provision of safety equipment for the prevention of accidents in preschool children and the impact of socioeconomic characteristicsThe motivating example for this paper comes from an evaluation of the effectiveness of home safety education and the provision of functioning smoke alarm safety devices for the prevention of accidents in preschool children. Studies were identified as part of a more general and updated Cochrane systematic review of safety equipment [10,19]. The primary intention of this review was to obtain IPD from all relevant studies and to subsequently synthesise these in a meta-analysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation